Abuse of Authority in Position and Redemption of Credit Fictitious Apparatus for Civil State (ASN) PD. Bank Perekreditan Rakyat (BPR) Sumber, Cirebon District - Kustriyo Kustriyo; Aryani Witasari (Jurnal Daulat Hukum, 2018)
Lending procedures are stages that must be passed before anything was decided to disbursed credits. The purpose is to facilitate banks in assessing the feasibility of a loan application. Prospective borrowers other than credit include the applicant's name or the desired customer also lists the number of credits / loans and other types of credit, which in this case is the customer debtors State Civil Apparatus (ASN) which will apply for credit in PD. BPR Sumber Cirebon. ASN in filing the credit of course have to ensure a decree to PD. BPR Sumber and must go through the stages prescribed by the PD. BPR Sumber. However, employees of PD. BPR Sumber in this case Head of Credit and Marketing Division has abused his authority and unfreeze credit by means of fictitious proposed by ASN using fictitious data. Thus resulting in no small loss in PD. BPR Sumber and the act was qualified as a criminal offense Banking. Basic judges in the court verdict should be based on theory and research results related to each other to obtain the maximum results of research and balanced at the level of theory and practice. Since the purpose of the law itself to fairness, expediency and legal certainty.Keywords: Position; Authority; Fictitious Credit; BPR.